Surgical treatment of traumatic eventration with polyester button and polypropylene mesh to strengthen the suture technique in equine. Issue 1 (December 2016) - Orlandini, Carla; Steiner, Denis; Boscarato, André; Gimenes, Gabriel; Alberton, Luiz
Abstract Background Defects in the abdominal wall of horses have high relapse rate. This is mainly in lateral eventrations and hernias caused by trauma from kicks of other horses or installation structures. The eventration region normally becomes swollen and there may be complications due to intestinal loop incarceration. The surgical treatment, consisting of reconstruction of the abdominal wall, frequently require biological or synthetic materials for the reinforcement of the suture line and tension support. Therefore, several studies have reported new materials for the repair of the abdominal wall, with the aim of improving the integration among adjacent tissues and reducing risks and complications such as rejection and infection. This report describes for the first time the use of a regular polypropylene mesh reinforced with polyester buttons for the herniorrhaphy. Case presentation A male, three-year-old, Appaloosa with 500 Kg presented to our hospital with a 10 days history of an increased volume on the left ventro-lateral region of the abdomen. During the physical examination, a deventration following traumatic rupture of the abdominal wall was diagnosed via ultrasonography. Then, the equine was anesthetized and moved to surgery for correction of the eventration which was performed according to conventional technique described in literature. Two days later, an eventration relapse was observed and confirmed via ultrasonography. After that, a second surgical intervention was performed using polyester buttons and polypropylene mesh. After the second surgical procedure, no complications related to eventration were observed either intra or postoperatively. After that, a recheck was performed thirty days later where satisfactory wound healing and total recovery were observed. Conclusion The use of polypropylene mesh reinforced with polyester buttons is an effective technique for the repair of traumatic eventration in horses. This technique provides effective reinforcement against the abdominal tension and was a good option for reconstruction of lacerated muscles in cases of equine post-traumatic eventration, including relapsing cases.